Revitalizing Soil Health with Regenerative Agriculture - Himanshu Pathak (Journal of the Indian Society of Soil Science, 2026)
Agricultural landscapes around the world are changing. There are increasing concerns of degraded soils, dwindling groundwater, polluting air and reducing biodiversity. In India, over 50% of the population engages in agriculture, therefore, this paradigm is becoming very critical. Out of 140 million hectares of cultivated land, more than 90 million hectares are degraded in terms of soil organic matter and fertility. Chemical dependency, declining crop yield, and shocks resulting from climate change are the challenges that farmers faced with regularly. A fundamental shift from extractive, linear systems to circular, regenerative models that generate system resilience is needed to address contemporary soil health issues.